Glue-assisted grinding exfoliation of large-size 2D materials for insulating thermal conduction and large-current-density hydrogen evolution. (December 2021) - Yang, Liusi; Wang, Dashuai; Liu, Minsu; Liu, Heming; Tan, Junyang; Wang, Zhongyue; Zhou, Heyuan; Yu, Qiangmin; Wang, Jingyun; Lin, Junhao; Zou, Xiaolong; Qiu, Ling; et al.
Graphical abstract: Abstract: Two-dimensional (2D) materials have many promising applications, but their scalable production remains challenging. Herein, we develop a glue-assisted grinding exfoliation (GAGE) method in which the adhesive polymer acts as a glue to massively produce 2D materials with large lateral sizes, high quality, and high yield. Density functional theory simulation shows that the exfoliation mechanism involves the competition between the binding energy of selected polymers and the 2D materials which is larger than the exfoliation energy of the layered materials. Taking h-BN as an example, the GAGE produces 2D h-BN with an average lateral size of 2.18 μm and thickness of 3.91 nm. The method is also extended to produce various other 2D materials, including graphene, MoS2, WS2, Bi2 O2 Se, mica, vermiculite, and montmorillonite. Two representative applications of thus-produced 2D materials have been demonstrated, including 2D h-BN/polymer composites for insulating thermal conduction and 2D MoS2 -based electrocatalysts for large-current-density hydrogen evolution, indicating the great potential of massively produced 2D materials.